Prognostic significance of EGFR, AREG and EREG amplification and gene expression in muscle invasive bladder cancer - Uysal, Daniel; Thaqi, Blerta; Fierek, Alexander; Jurgowski, David; Popovic, Zoran V.; Siegel, Fabian; Michel, Maurice Stephan; Nuhn, Philipp; Worst, Thomas; Erben, Philipp; Nitschke, Katja (Frontiers in oncology, 2024)
Introduction: Muscle invasive bladder cancer (MIBC) remains a prevalent cancer with limited therapeutic options, obviating the need for innovative therapies. The epidermal growth factor receptor (EGFR) is a linchpin in tumor progression and presents a potential therapeutic target in MIBC. Additionally, the EGFR ligands AREG and EREG have shown associations with response to anti-EGFR therapy and improved progression-free survival in colorectal carcinoma. Materials and methods: We investigated the prognostic significance of EGFR, AREG, and EREG in MIBC. Gene expression and copy number analyses were performed via qRT-PCR on tissue samples from 100 patients with MIBC who underwent radical cystectomy at the University Hospital Mannheim (MA; median age 72, interquartile range [IQR] 64–78 years, 25% female). Results were validated in 361 patients from the 2017 TCGA MIBC cohort (median age 69, IQR 60–77 years, 27% female), in the Chungbuk and MDACC cohort. Gene expressions were correlated with clinicopathologic parameters using the Mann-Whitney test, Kruskal-Wallis- test and Spearman correlation. For overall survival (OS), cancer-specific survival (CSS) and disease-free survival (DFS) gene expression was analyzed with Kaplan-Meier and Cox-proportional hazard models. Results: Significant gene expression differences in EGFR, AREG, and EREG could be detected in all cohorts. In the TCGA cohort, EGFR expression was significantly elevated in patients with EGFR amplification and KRAS wildtype. High AREG expression independently predicted longer OS (HR = 0.35, CI 0.19 - 0.63, p = 0.0004) and CSS (HR = 0.42, CI 0.18 – 0.95, p = 0.0378) in the MA cohort. In the TCGA cohort, high EGFR, AREG, and EREG expression correlated with shorter OS (AREG: HR = 1.57, CI 1.12 – 2.20, p = 0.0090) and DFS (EGFR: HR = 1.91, CI 1.31 – 2.8, p = 0.0008). EGFR amplification was also associated with reduced DFS. Discussion: High EGFR and EREG indicate worse survival in patients with MIBC. The prognostic role of AREG should further be investigated in large, prospective series. Divergent survival outcomes between the four cohorts should be interpreted cautiously, considering differences in analysis methods and demographics. Further in vitro investigations are necessary to elucidate the functional mechanisms underlying the associations observed in this study.
Gesehen am 21.10.2024